2017
DOI: 10.1093/icvts/ivx400
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after complete resection of non-small-cell lung cancer in patients with interstitial lung disease

Abstract: The presence of ILD led to a much poorer survival after complete resection of non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Tzouvelekis et al [ 12 ], recently reported a median survival of 14 months in patients with lung cancer and IPF from the time of lung cancer diagnosis. Sekihara et al [ 13 ], reported 5 year-overall survival of 40% in patients with lung cancer and ILD as opposed to 72% in those with lung cancer only without ILD. A meta-analysis done by Koo et al [ 7 ], showed lower survival rate in patients with lung cancer and CPFE as compared to those with lung cancer only and those with lung cancer and emphysema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tzouvelekis et al [ 12 ], recently reported a median survival of 14 months in patients with lung cancer and IPF from the time of lung cancer diagnosis. Sekihara et al [ 13 ], reported 5 year-overall survival of 40% in patients with lung cancer and ILD as opposed to 72% in those with lung cancer only without ILD. A meta-analysis done by Koo et al [ 7 ], showed lower survival rate in patients with lung cancer and CPFE as compared to those with lung cancer only and those with lung cancer and emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was found in the survival rate amongst the patient groups of lung cancer and the 4 different categories of ILD according to the diagnosis of IPF in both unadjusted and adjusted cox regression model. Similarly, Sekihara et al reported no significant difference in the overall survival between patients with UIP pattern (41%) and those with non-UIP (possible UIP and inconsistent with UIP patterns) (41%) [ 13 ]. Maybe larger number of patients in future studies will be able to detect significant differences amongst the different types of ILD documented on CT.…”
Section: Discussionmentioning
confidence: 99%
“…Several case-control studies on Asian IPF patients, mostly unmatched, have been published. Authors of studies on surgically treated LC patients reported that IPF or ILD was associated with shorter survival and that the presence of either pattern was an independent prognostic factor [32][33][34][35]. For chemotherapy-treated patients, IPF or idiopathic ILD was an unfavorable factor for survival [15,36].…”
Section: Discussionmentioning
confidence: 99%
“…Among previous studies that examined the survival of patients with IP after undergoing NSCLC resection [ 4 , 5 , 15 - 17 ], they examined the prognostic roles of clinicopathological factors, including Krebs von den Lungen-6 (KL-6), but not tumor markers. Therefore, in the present study, we examined the prognostic significance of serum tumor markers, and found that serum CEA level might serve as an efficient prognostic indicator after surgery in NSCLC with IP.…”
Section: Discussionmentioning
confidence: 99%